Intervención fisioterapéutica en paciente masculino de 17 años con fractura de clavícula. - Patín Pasto, Cristian Paul (2024)
This clinical case describes the absolute evaluation of the patient, including his medical history, lifestyle habits, as well as the results of physical and radiological examinations that confirmed the diagnosis of clavicle fracture. Additionally, the functional limitations that the patient has as a result of this injury are detailed. This includes a bulge on the right anterosuperior surface at the level of the thorax. The approach in "Physiotherapeutic Intervention in the 17-year-old male patient with clavicle fracture" is based on the great need to address the complexities and challenges presented by clavicle fracture. Although this type of bone injury is considered relatively common, its impact should not be underestimated due to its critical anatomical location, as well as its direct influence on the functionality of the shoulder and arm. In the development of this case study, it was based on the lines of research of the physiotherapy course of the Faculty of Health Sciences, which refers to the Physiotherapeutic treatment in the 17-year-old male patient with a clavicle fracture. In the focus of this study, positive evolution was observed in the rehabilitation of the patient diagnosed with right clavicle fracture. The results demonstrate that a comprehensive physiotherapy treatment approach has been effective in addressing the complications associated with this injury. The implementation of a constantly supervised and personalized therapeutic exercise plan facilitated improvements specifically in the joint mobility and muscle strength of the affected limb, in this way the follow-up under thorough documentation supports the effectiveness of the treatment in the present case study.